1980
DOI: 10.1128/jcm.11.3.286-291.1980
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid requirements of Legionella pneumophila

Abstract: The amino acids required for growth and as energy sources by 10 strains of Legionella pneumophila were determined by using a chemically defined medium. All strains required arginine, cysteine, isoleucine, leucine, threonine, valine, methionine, and phenylalanine or tyrosine. Most strains (7 of 10) required serine, and two strains had to be supplied proline before growth could be established. All 10 strains used serine and, to a lesser extent, threonine as the sole sources of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 8 publications
2
61
0
2
Order By: Relevance
“…The nature of the energy and carbon sources utilized by intracellular L. pneumophila is only partially known. Based on studies of broth cultures, the bacterium is thought to utilize only amino acids, mainly serine (Pine et al, 1979;George et al, 1980). Indeed, during the RP in amoebae, genes corresponding to many of its amino acid degradation pathways are upregulated (Table S3A).…”
Section: The Diet Of Intracellular L Pneumophila: Robbery Of Host Ammentioning
confidence: 99%
“…The nature of the energy and carbon sources utilized by intracellular L. pneumophila is only partially known. Based on studies of broth cultures, the bacterium is thought to utilize only amino acids, mainly serine (Pine et al, 1979;George et al, 1980). Indeed, during the RP in amoebae, genes corresponding to many of its amino acid degradation pathways are upregulated (Table S3A).…”
Section: The Diet Of Intracellular L Pneumophila: Robbery Of Host Ammentioning
confidence: 99%
“…Legionella pneumophila relies on amino acids as the main source of energy and carbon, although carbohydrates may be a minor substrate (George et al, 1980;Ristroph et al, 1981;Tesh and Miller, 1981;Eylert et al, 2010). Even though L. pneumophila preferentially utilizes amino acids for carbon and energy, in silico analysis of the L. pneumophila genome sequence revealed that this organism is auxotrophic for the seven amino acids Arg, Cys, Ile, Leu, Met, Thr and Val (Cazalet et al, 2004;Chien et al, 2004).…”
Section: Amino Acid Requirements Of L Pneumophilamentioning
confidence: 99%
“…Even though L. pneumophila preferentially utilizes amino acids for carbon and energy, in silico analysis of the L. pneumophila genome sequence revealed that this organism is auxotrophic for the seven amino acids Arg, Cys, Ile, Leu, Met, Thr and Val (Cazalet et al, 2004;Chien et al, 2004). Furthermore, it has been shown that the amino acids Arg, Cys, Ile, Leu, Met, Ser, Thr and Val are essential for growth of L. pneumophila in vitro (Pine et al, 1979;George et al, 1980;Reeves et al, 1981;Ristroph et al, 1981;Tesh and Miller, 1981;Tesh et al, 1983;Molofsky and Swanson, 2004;Wieland et al, 2005;Eylert et al, 2010). The four amino acids, Arg, Cys, Gln and Ser, are needed to support growth in vivo (Wieland et al, 2005).…”
Section: Amino Acid Requirements Of L Pneumophilamentioning
confidence: 99%
See 2 more Smart Citations